A new apterous rove beetle genus (Coleoptera: Staphylinidae) from the Northern Andes with an assessment of its phylogenetic position - Chatzimanolis, Stylianos; Brunke, Adam J. (European Journal of Taxonomy, 2021)
A remarkable new apterous genus of Xanthopygina beetles is described here as Ikaros gen. nov. The new genus includes three new species, I. apteros gen. et sp. nov. from Colombia, I. paramo gen. et sp. nov. from Colombia and I. polygonos gen. et sp. nov. from Venezuela. Phylogenetic analyses using molecular and morphological data were performed to assess the phylogenetic position of Ikaros gen. nov. and whether the three new taxa formed a monophyletic group. All analyses, including those with aptery-associated characters removed, strongly supported the monophyly of Ikaros gen. nov. The genus could not be confidently resolved as a member of any of the existing genus-group lineages, likely due to a lack of morphological signal in the backbone of the tree. Further analyses, ideally with molecular data, are needed to determine the position of Ikaros gen. nov.